A study on the effects of using phoneme-grapheme correspondence method on sound recognition ability of efl 10th-Grade students at Quoc Oai high school and their attitudes - Nguyễn, Thị Thơm (University of Languages and International Studies, 2017)
This minor thesis was carried out with an attempt to investigate the effects of Phoneme - Grapheme Corr espondence Method on sound recognition ability of EFL 10 th - grade students at Quoc Oai High School and their attitudes . The research design us ed in the study was a quasi - experimental pre - test, post - test, non - equivalent group design including one experimenta l group and one control group. A total of 75 10 th - grade students took part in the study. The instrument s used for the study w ere a 2 0 - multiple - choice - item test in phonetics and a questionnaire . The results obtained from the analyzed data show that Phoneme - Grapheme Correspondence method had a significant effect on the improvement in students‟ sound recognition ability. Furthermore, students show positive attitudes towards this method